UPAYA IFC (INDONESIAN FASHION CHAMBER) DALAM MEWUJUDKAN INDONESIA SEBAGAI “THE FASHION MUSLIM CENTER OF THE WORLD 2025” - Rima Sartika Ulfa; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The development of the fashion world continues to increase, starting from technology and media so that various modes and styles as well as clothing are also social symbols so as to provide a cultural identity to someone. Regarding the aim of the study to find out which developments in fashion hijab in Indonesia, find out IFC (Indonesian Fashion Chamber) in realizing Indonesia as the